AB0767 MULTI-SYMPTOM IMPACT ON THE EQ-5D INDEX IN BIO-NAÏVE ACTIVE PSORIATIC ARTHRITIS PATIENTS: AN ANALYSIS THROUGH WEEK 24 OF THE GO-VIBRANT STUDY. (June 2019) - Ogdie, Alexis; Nan, LI; Peterson, Steve; Karyekar, Chetan; Chakravarty, Soumya D.; Kafka, Shelly; Walsh, Jessica a.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory disease characterized by peripheral arthritis, axial inflammation, dactylitis, enthesitis and skin and nail psoriasis. The impact of skin and joint components of the disease on patient health-related quality of life has been described in previous research (1, 2) but the impact of other major clinical manifestations has not been similarly characterized. Objectives: To quantify the impact of the major clinical manifestations of PsA on patient reported health related quality of life, as estimated by disease state preference (utility) derived from the EQ-5D index in a randomized clinical trial. Methods: This analysis used data from a multicenter, randomized, double-blind, placebo-controlled trial of intravenous (IV) Golimumab in biologic naïve patients with active psoriatic arthritis (GO-VIBRANT study). Patient baseline characteristics of the GO-VIBRANT study population have been previously described (3). Core outcome measures recommended by OMERACT (Outcome Measures in Rheumatology Clinical Trials) and guideline on utility mapping by ISPOR (International Society for Pharmacoeconomics and Outcome Research) were used to guide initial attribute selection. Utility was derived from patient responses to the EQ-5D index, which assesses mobility, self-care, usual activities, pain/discomfort, and anxiety/depression, and was completed at weeks 0, 8, 14, and 24 in the trial (placebo-controlled period). EQ-5D index is used as a measure of overall health and is an outcome commonly used in health economic analyses. Multivariate analysis was performed using a Mixed-Effect Repeated Measures model based on observed data until week 24 in pooled patient population. Results: Based on univariate analyses and evaluation of collinearity between variables, the following attributes were included in the multivariate models: age, gender, region, PsA disease duration, PASI score, enthesitis, dactylitis, tender joint count (TJC), swollen joint count (SJC), C-reactive protein (CRP mg/L) and Health assessment Questionnaire-Disability index (HAQ-DI). In the final model, PASI score (β=-0.00126, p=0.0006), enthesitis (β=-0.01237, p=0.03), TJC (β=-0.00112, p<0.0001), CRP (β=-0.00079, p<0.0001) and HAQ-DI (β=-0.1664, p<0.0001) were all statistically significantly associated with the EQ-5D index. A sensitivity analysis among a subgroup of patients who had spondylitis with peripheral joint arthritis as their primary arthritic presentation of PsA showed that spinal pain (β=0.0101, p<0.0001), as measured by question #2 of the Bath ankylosing Spondylitis Disease activity index (BASDAI), was also statistically significantly associated with the EQ-5D index in the multivariate model. Conclusion: Multiple PsA clinical manifestations including psoriasis, enthesitis, TJC, spinal pain, CRP, and physical function were statistically significantly associated with utility among PsA patients as derived from the EQ-5D index. These findings indicate that consideration of multiple clinical manifestations of PsA is warranted when evaluating the impact of PsA on patients. References: [1] Borman P, et al. Clin Rheumatol. 2007;26(3):330–4. [2] de Vlam K, et al. Rheumatol ther. 2018;5(2):423–36. [3] Kavanaugh a, et al. Arthritis Rheumatol. 2017Nov;69(11):2151-2161. Disclosure of interests: Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: abbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: abbVie, amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer inc, Takeda, Consultant for: abbvie, amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: abbvie, amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Nan Li Shareholder of: J&J, Employee of: Janssen Scientific affairs, LLC, Steve Peterson Shareholder of: Janssen, Employee of: BMS (2000-2002), Janssen (2002-present), Chetan Karyekar Shareholder of: J&J, Employee of: Janssen Scientific affairs, LLC, abbott, BMS, Novartis, Soumya D Chakravarty Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Shelly Kafka Shareholder of: J&J, Employee of: J&J, Jessica a. Walsh Grant/research support from: abbvie, Pfizer, Consultant for: abbvie, Celgene, Lilly, Novartis